1996
DOI: 10.1063/1.472399
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study of CH4 dissociation on pure and gold-alloyed Ni(111) surfaces

Abstract: We present a density functional theory study of the first step of CH 4 adsorption on the Ni͑111͒ surface, dissociation into adsorbed CH 3 and H. The rupture of the C-H bond occurs preferentially on top of a Ni atom, with a dissociation barrier of about 100 kJ/mol ͑including zero point corrections͒. The transition state involves considerable internal excitation of the molecule. The active C-H bond is both stretched to 1.6 Å and tilted relative to the methyl group. A normal mode analysis shows that the reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
90
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(108 citation statements)
references
References 45 publications
(94 reference statements)
17
90
1
Order By: Relevance
“…The decrease in the catalytic activity of the 3Au-3Mo-Ni/GDC sample with respect to the non-modified Ni/GDC is in accord with the d-band center theory proposed by Norskov et al (Kratzer et al, 1996;Nørskov et al, 2011) and specifically dealing with the dissociation and dehydrogenation of CH 4 on the Au doped Ni surface. They proposed that the rate of CH 4 dehydrogenation will be retarded on the Au modified surface, due to the fact that the center of the d-band density of states shifts to lower energy below the Fermi level with respect to Ni.…”
Section: Electrocatalytic Stability Of Ni-au-mo/gdcsupporting
confidence: 66%
“…The decrease in the catalytic activity of the 3Au-3Mo-Ni/GDC sample with respect to the non-modified Ni/GDC is in accord with the d-band center theory proposed by Norskov et al (Kratzer et al, 1996;Nørskov et al, 2011) and specifically dealing with the dissociation and dehydrogenation of CH 4 on the Au doped Ni surface. They proposed that the rate of CH 4 dehydrogenation will be retarded on the Au modified surface, due to the fact that the center of the d-band density of states shifts to lower energy below the Fermi level with respect to Ni.…”
Section: Electrocatalytic Stability Of Ni-au-mo/gdcsupporting
confidence: 66%
“…The initial sticking probability of methane on a Ni surface with just 0.25 ML of gold fell to ~1 0% of the sticking value of the clean Ni(111) surface (166). DFT calculations revealed that the CH4 dissociation barrier on a Ni atom increased by 16 kJ/mol when a single Au neighbor was present (167). Two neighboring gold atoms, resulted in a 38 kJ/mol increase (the barrier to dissociation on a Ni(111) atom was calculated to be ~1 00 kJ/mol).…”
Section: 4mentioning
confidence: 96%
“…To correlate the electronic structure of the surface and its catalytic properties, the d-band center partly describing the electronic effect of the surface, is calculated by the formula 25,26…”
Section: Computational Methods and Modelsmentioning
confidence: 99%